Application of diode laser in the management of giant rhinophyma - Kamiński, Bartłomiej (Dermatology Review/Przegląd Dermatologiczny, 2025)
Nasal rhinophyma represents the phymatous stage of rosacea. The primary concern in patients with giant rhinophyma is social isolation, as – apart from the pronounced cosmetic disfigurement – it does not cause other physical complaints. The aim of this paper is to reach the broadest possible group of otolaryngologists, general practitioners, dermatologists, and other specialists by demonstrating that a procedure performed under local anesthesia using a diode laser can significantly improve patients’ quality of life, offering the possibility of emerging from complete social isolation and returning to normal daily functioning.